2019
DOI: 10.1038/s41598-019-45672-4
|View full text |Cite
|
Sign up to set email alerts
|

Seebeck-voltage-triggered self-biased photoelectrochemical water splitting using HfOx/SiOx bi-layer protected Si photocathodes

Abstract: The use of a photoelectrochemical device is an efficient method of converting solar energy into hydrogen fuel via water splitting reactions. One of the best photoelectrode materials is Si, which absorbs a broad wavelength range of incident light and produces a high photocurrent level (~44 mA·cm −2 ). However, the maximum photovoltage that can be generated in single-junction Si devices (~0.75 V) is much lower than the voltage required for a water splitting reaction (>1.6 V). In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Considering these factors, the energy conversion efficiency of TE device (5–10%) is low, compared to PVs (up to 46%) [ 159 ]. Therefore, several researches have demonstrated that by combing TE and PEC reaction, the utilization efficiency for both solar energy harvest and water splitting can reach a high content [ 160 ]. The first proposed the combination of PEC and photothermal-electrochemical cycles for H 2 production by solar energy was by Nikola Getoff in 1984 [ 161 ], which was in acid aqueous solution using I 2 and I 3 − acting as a sensitizer with the existence of ferrous ions.…”
Section: Water Splitting Driven By Thermoelectric Devicementioning
confidence: 99%
“…Considering these factors, the energy conversion efficiency of TE device (5–10%) is low, compared to PVs (up to 46%) [ 159 ]. Therefore, several researches have demonstrated that by combing TE and PEC reaction, the utilization efficiency for both solar energy harvest and water splitting can reach a high content [ 160 ]. The first proposed the combination of PEC and photothermal-electrochemical cycles for H 2 production by solar energy was by Nikola Getoff in 1984 [ 161 ], which was in acid aqueous solution using I 2 and I 3 − acting as a sensitizer with the existence of ferrous ions.…”
Section: Water Splitting Driven By Thermoelectric Devicementioning
confidence: 99%
“…Many of these layers also provide an additional band bending and hence enhance the photocurrent and onset potential of the whole photocathode stack, increasing the attractiveness of using such a layer. Overlayers such as TiO 2 , In 2 S 3 , ZnS, HfO 2 , , and Al 2 O 3 , have demonstrated almost no degradation in the various testing durations mentioned in the many works cited. On the other hand, due to the inherent stability of metal oxides in water, most photoanodes do not require complex protection and have high stabilities in most electrolytes. , …”
Section: Applicationsmentioning
confidence: 99%
“…The sunlight is used to separate water by using specialized semiconductors knows as photoelectrochemical materials in PEC reaction. The use of TEC with PEC leads to maximize the solar energy harvest and enhance the performance of electrolysis process [18].…”
Section: Thermoelectric (Te) Devicesmentioning
confidence: 99%